Study on assessment of water system health in Heihe River Basin based on the game theory - Jiayu Du; Hairong Gao; Ran Liu; Yu Han; Runzhi Hu (Ecological Indicators)
Maintaining river health holds significant implications for guaranteeing the proper functioning of water systems and promoting social development. The construction and restoration of the river environment has emerged as a hot issue, and conducting an assessment study of water system health plays a crucial role in quantitatively describing water system health problems and providing a basis for related governance activities. Taking the Heihe River Basin in Gansu Province as the study area, this study conducts an assessment based on the Index System Method. By combining Game Theory Combinatorial Weighting Method, “Punishment-Incentive Variable Weight Model”, and the Fuzzy Matter-Element Extension Method, a comprehensive assessment process with scientific accuracy and high applicability to the “environment + management” situation of regional environmental conditions is established. In addition, satellite remote sensing technology is introduced, utilizing Sentinel-2 satellite remote sensing imagery in combination with linear fitting, curve fitting, and algorithm fitting to establish regional models for water quality indicators. Modelling and assessment calculation process to form a study system for evaluating and governing the health of the water system in the Heihe River Basin in Gansu Province. The study presents multi-indicator inversion models for watershed water quality, with XGBoost showing the best performance. Model accuracies (R2) for TN, pH, Chl-a, and Tur exceed 0.7. Preliminary analyses using the above ideas suggest that the current basin water system is most likely to be in a “health” condition, and it is noted that regional management prioritizes water system connectivity and biological resource protection.and that this study system can subsequently provide guidance for local long-term construction and management.